SP4 Implementation of smart-pumps and standard concentration infusions across a paediatric hospital group – a training and evaluation model. Issue 5 (20th April 2022) - Howlett, Moninne; McGrath, Eimear; Sutton, Sharon; Aughey, Kate; Higgin, Rebecca; Breatnach, Cormac
Abstract : Aim: To implement and train staff in the use of a smart-pump drug library across all clinical areas of the four sites of a large paediatric hospital group. Method: A multi-disciplinary steering group was devised with representation from each site to co-ordinate the implementation of a smart-pump drug library and smart-pumps across the entire organisation. Two stages of training were identified: Phase 1: smart-infusion pump training to new users; Phase 2: drug library education. Phase 2 training was co-ordinated by a dedicated smart-pump team nurse educator, supported by six nursing staff seconded to the project on a short-term basis. A comprehensive training package and support documentation were developed. Drug library education sessions involved interactive practical teaching sessions in use of the drug library, followed by completion of a self-assessment competency tool. Staff training was recorded in a training record database. Implementation into each clinical area occurred once 80% of staff had attained competency in both pump and drug library training. Amended training sessions were offered to pharmacy staff and to nursing students. A 12-month fixed term full-time Smart-Pump Support Clinical Nurse Manager post was created and filled in Q3 2020 to support staff and the smart-pump team and to conduct post-implementation audit. Efficacy of training and compliance of drug library use were evaluated at 3-month and 9-month intervals using staff satisfaction surveys and direct observational study. Results: Drug library training was delivered to over 800 nursing staff between June 2020 and August 2021. The drug library has been implemented in all clinical areas across four sites. Processes for on-going training support have been established. Preliminary direct observational study results indicate that drug library use increased from 41.2% to 73.5% at 3 months and 9 months respectively. Where the drug library was used, no clinically significant programming errors were identified. IV fluids were most commonly programmed outside of the drug library. The most common deviations involved use of the incorrect care unit. The 9-month audit is ongoing. Staff satisfaction survey was completed by 140 staff 3 months post implementation. 80% of staff surveyed agreed the drug library was easy to programme, with 84% agreeing that the drug library enhances patient safety and 89% considering education was good/excellent. Phase 2 (9 months' post implementation) is ongoing. Conclusion: Cross-site collaboration has enabled wide scale implementation of internationally recognised best practices for the safe administration of IV medications across the four paediatric sites of a large paediatric hospital group. 1–3 Feedback provided to the smart-pump team and local pharmacy and nursing teams has facilitated ongoing development of education and training needs and drug library content. Training continues to be offered to all new staff, with local refresher training available on request. Dedicated nursing resources are an essential component for successful implementation of smart-pumps at an organisational level. References: Institute for Safe Medication Practices, ISMP. Guidelines for Optimizing Safe Implementation and Use of Smart Infusion Pumps 2020. Available at: https://www.ismp.org/guidelines/safe-implementation-and-use-smart-pumps Royal College of Paediatrics and Child Health (RCPCH)/Neonatal Paediatric Pharmacists Group (NPPG). Standardising intravenous infusion concentrations in children in the UK 2021. Available at: https://www.rcpch.ac.uk/resources/standardising-intravenous-infusion-concentrations-children-uk American Society of Health-System Pharmacists, ASHP. Standardize 4 Safety 2018. Available at: https://www.ashp.org/pharmacy-practice/standardize-4-safety-initiative